Modern approaches to the management of gender dysphoria from endocrinologist`s viewpoint: clinical case - N. I. Volkova; I. Yu. Davidenko; Yu. S. Degtyareva (Медицинский вестник Юга России, 2022)
Providing medical care to people with gender dysphoria is a complex multidisciplinary task, the success of which is determined by the close cooperation of specialists qualified in helping such patients, such as a psychiatrist, endocrinologist, and surgeon. In addition to diagnostic testing, patients with gender dysphoria require psychotherapy or psychological counseling, hormone replacement therapy, and, if necessary, gender confirmation surgery. Before prescribing hormone therapy, it is necessary to make sure that the patient meets the criteria for the diagnosis of gender dysphoria, to be sure that the patient’s desire to change gender is justified, all the consequences of therapy, including possible physical changes and the timing of their occurrence, are explained. Genital reconstruction procedures are possible only after at least one year of hormone therapy and life in the role of the chosen gender. The algorithms of medical care for persons with gender dysphoria developed to date describe in detail the mechanism of gender reassignment, the contribution of various specialists to this process, as well as possible risks and methods for their prevention. Only careful observance of the stages of diagnosis and treatment without violating their sequence can lead to the successful achievement of the result. while any deviations from the algorithms, due to objective and subjective reasons, entail serious life-threatening consequences, which is clearly demonstrated in the clinical cases presented in this article.